Purification of stevia extract by chitosan precipitation and reversed‐phase chromatography. (21st January 2021) - Zhang, Menglei; Hua, Xiao; Liu, Yaxian; Wang, Zijie; Wang, Mingming; Yang, Ruijin
Summary: To improve the shortness of the current purification technology of steviol glycosides (SG) extract, a two‐step purification procedure consisting of chitosan precipitation and reversed‐phase chromatography (RPC) was investigated. The impurity‐to‐SG ratio in the SG extract obtained from non‐destructive soaking was 5:1 6:1. It was found that 80.90% of the impurities could be removed by RPC using 20% (v/v) ethanol solution as the eluent with a high SG recovery of 96.98%. When 25% ethanol was applied, the SG recovery was reduced to 71.23%. An adsorption test using D280 anionic resin suggested that the impurities were negatively charged; thus, chitosan was used to co‐precipitate the impurities. An optimal decolourisation result of 70% was obtained at 0.06 g·g −1 (w/w, to solids in extract) chitosan addition, shaking at 28 °C for 1 h. Afterwards, the extract was further purified by RPC. The total removal rate of impurities was increased to 91.20%, and the SG recovery was 85.15%. Abstract : Two‐step purification procedure consisting of chitosan precipitation and reversed‐phase chromatography (RPC) was investigated. In the first step, chitosan was used to remove negatively charged proteins and polyphenols in the water extract according to the chargeability. After the preliminary purification, the NDR‐1 resin was used to further remove the remaining protein according to the polarity difference of the protein and glycoside.